Bridging gaps: the intersection of women in engineering and gender studies—challenges, advances, and future directions - Daniel Raphael Ejike Ewim; Akinola George Dosunmu (Discover Global Society)
Abstract Despite growing awareness, the underrepresentation of women in the engineering profession remains a persistent global issue, reflecting broader gender inequalities in STEM fields. This paper explores the intersection of women and engineering, employing a gender study lens to synthesize existing research and analyze challenges, initiatives, and future directions in this context. It contextualizes systemic barriers such as implicit biases, gendered stereotypes, and the sticky wall phenomenon, as well as intersectional dimensions impacting marginalized groups. The paper evaluates organizational policies, educational reforms, and workplace strategies to foster inclusivity for women in the sciences. By integrating insights from gender studies, the analysis highlights critical gaps in the current literature. It proposes inclusive strategies to advance the equity and representation of women in the engineering profession. This study seeks to guide future research and inform policy implementation through a multidisciplinary approach, promoting diversity and inclusivity in engineering professions worldwide.